Analysis of Syekh Taqiyuddin An-Nabhani's Idea on Public Assets Privatization - Dodi Okri Handoko; Juliana Juliana; Fahmy Lukman (Islamic Research, 2021)
In Indonesia, public asset privatization policy has been valid since the Oil and Gas Law Number 22 the Year 2001. The objectives of this research were: (1) To determine the criteria for public assets according to the idea of Syekh Taqiyuddin An-Nabhani., (2) To find out the Islamic economic analysis of the idea of Syekh Taqiyuddin An-Nabhani on the privatization of public assets. The data source of this research is secondary data, which were taken from literature and books from research correlating to the object of this study and other required data. The data analysis in this research is descriptive. First, various data collected were analyzed using content analysis technique (content analysis), then the study and analysis of the data are carried out to obtain the conclusions. After conducting the research and analysis, it is concluded that (1) Syekh Taqiyuddin An-Nabhani classifies public assets based on the types of ownership, namely public ownership and state ownership, (2) Islam strongly prohibits the management of public assets through privatization. However, it is returned to the State, and its use by the public is permitted by shara'.